The impact of blood flow restriction combined with variable resistance training at different loads on lower limb strength and explosiveness in collegiate basketball players - Peng, Wuwen; Zhang, Zhanming; Lu, Di; Li, Zhentao; Li, Guoxing; Sun, Jian; Li, Duanying (Frontiers in Physiology, 2025)
This study compared the effects of an 8-week program of low-load blood flow restriction training combined with chain-based variable resistance training (BFR-VRT) and high-load chain-based variable resistance training (VRT) on lower-limb performance in male college basketball players. A total of 27 players were randomly assigned to the BFR-VRT group (n = 9), the variable resistance training group (n = 9), or a control group (n = 9). The BFR-VRT protocol used pneumatic cuffs applied to the proximal thighs, with training pressure set at 180 mmHg, and combined a 10% 1RM barbell load with 10%–30% 1RM from chains, whereas the VRT protocol consisted of a 55% 1RM barbell load plus 10%–30% 1RM from chains. The control group did not receive any resistance training. Repeated-measures Repeated-measures ANOVA showed significant within-group improvements in SQ-1RM, LTC, RTC, countermovement jump, squat jump, DJ-RSI, standing long jump, and 30-m in both the BFR-VRT and VRT groups (all p < 0.05), whereas the CON group showed no significant change (p > 0.05). Between-group comparisons indicated no significant differences among the three groups on these outcomes (all p > 0.05). In conclusion, both BFR-VRT and VRT improved lower-limb performance; under a lower external load, BFR-VRT showed effects comparable to, or trending greater than, VRT on certain performance measures.Clinical Trial Registrationhttps://www.chictr.org.cn/showprojEN.html?proj=201896, identifier ChiCTR2400086132.